FINANCE AND MONEY CREDIT SYSTEM. BANKS AND THEIR ROLE IN THE MARKET ECONOMY (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2023)
At the same time, the successful implementation of reforms regarding the liberalization of the foreign exchange market is closely related to the effectiveness of measures to improve the monetary policy, strengthen the activities of commercial banks, and develop the banking system. It should be noted that the correct acceptance and support of the changes in the monetary and credit sphere by the population and business entities is of great importance in the new events taking place during the revision of approaches to the implementation of the economic policy.